The Effect of Karen's Model with Educational Tools on Female Students' Basketball Scoring Skills - Jassim, Mayada Khalid; Jaafar, Rashwan Muhammad (Indonesian Journal Publisher, 2024)
The importance of the research lies in learning peaceful scoring through Karen's model and using the auxiliary tool to teach this skill through motor sense and feeling the target, as well as preparing educational units specific to the model referred to in the research and identifying which of the two groups was better in implementing the units. This research used the experimental method, known for its precision and balance, to solve the research problem, selecting first-year students from Al-Mustansiriyah University. The sample included 15 students each in the experimental and control groups, representing 19.10% of the original 157 students. A pilot experiment involved 5 additional students from outside the sample. The use of Karen's model positively impacts the learning of peaceful scoring skills. Educational tools used with the model enhanced learning outcomes, showing significant improvements in the experimental group. Educational models should be reviewed and prioritized to enhance the learning process. Consider individual differences in understanding concept maps. Use engaging educational exercises with Karen's model to achieve better results, utilizing tools that capture learners' attention.